20. CURRENT STATUS OF NURSES' HEALTH EDUCATION KNOWLEDGE AND SOME RELATED FACTORS AT HA ĐONG GENERAL HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the health education knowledge of nurses and identify some related factors at Ha Dong General Hospital in 2023.Subjects and methods: Cross-sectional study design on 264 nurses working in clinical departments of Ha Dong General Hospital from November 2023 to November 2024. The interview toolkit was designed based on the content of health education skills with Cronbach's alpha coefficient = 0.807.Results: 89% of nurses have satisfactory knowledge in health counseling and education. Factors related to health education knowledge include: Professional qualifications and training in health education and counseling.Conclusion: Nurses' health education knowledge is quite high, it is necessary to focus on training to improve professional qualifications and health education knowledge for nurses.
Keywords: Knowledge; health education; nursing